2023
DOI: 10.1177/00302228231181256
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Serbian Version of the Death Attitudes Profile- Revised (DAP-R) Instrument

Abstract: The Death Attitude Profile-Revised (DAP-R), one of the most widely used scales for assessing death attitudes is a multidimensional questionnaire capable of measuring a wide range of attitudes towards death. The aim of our study was to assess the reliability and validity of the Serbian version of the DAP-R. The study was conducted in October 2022 and included a total of 547 students of the Faculty of Medicine University of Belgrade (FMUB). Based on Cronbach’s alpha coefficient values, our data show good reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Comparing the results of our research with the results from the Serbian DAP-Rs validation study on medical students, we observed some differences. HCPs working in the field of Palliative Medicine and Oncology, compared to medical students, showed significantly lower mean values for FD ( p = 0.00) and higher for NA domain ( p = 0.00) [ 24 ]. Similar results were obtained in this research when comparing physicians specialized in the field of Palliative Medicine and Oncology and those with other specializations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing the results of our research with the results from the Serbian DAP-Rs validation study on medical students, we observed some differences. HCPs working in the field of Palliative Medicine and Oncology, compared to medical students, showed significantly lower mean values for FD ( p = 0.00) and higher for NA domain ( p = 0.00) [ 24 ]. Similar results were obtained in this research when comparing physicians specialized in the field of Palliative Medicine and Oncology and those with other specializations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on highlighted data, the aim of this research was to determine attitudes toward death among HCPs who manage the care of patients with incurable diseases. To the authors’ knowledge, this is the first study conducted in the Western Balkan region, with the exception of Serbia, where the Serbian version of the Death Attitudes Profile-Revised (DAP-RSp) was validated by Maric et al in the population of medical students [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, attitudes to end-of-life care, death and dying in Serbia are unknown both among healthcare professionals and general population. The Serbian version of the Death Attitudes Profile Revised (DAP-RSp) Instrument is now available and should enable the assessment of attitudes towards death in healthcare professionals and in general population (18).…”
Section: Impact On End-of-life Carementioning
confidence: 99%